ANALISIS PENOLAKAN KLAIM ASURANSI JIWA BERDASARKAN KLAUSUL “CONTESTABLE PERIOD” (STUDI PUTUSAN NOMOR 489/Pdt.G/2021/PN Mdn) - Christian Batara Wishnu; Wetmen Sinaga; Paltiada Saragi (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2023)
Insurance Agreement is a reciprocal agreement carried out between the insured and the insured. This reciprocal agreement is a form of risk transfer carried out by the insured to the insurer in exchange for an amount of money or premium paid by the insured to the insurer. In practice special provisions regarding things that are prohibited to be done or things to be done are regulated by the insurer. In the life insurance agreement, there is a special clause, namely the "Contestable Period" which regulates the policyholder’s authority to review the correctness of the information provided by the insured and if these facts do not match the information provided at the time of filling out the SPAJ or other forms, the insurer has the right to cancel the coverage and is only obliged to return the investment value if any. The purpose and purpose of writing this thesis is to find out whether the "Contestable Period" clause is in accordance with the principles and objectives of the insurance business. The research method used is normative juridical research with a statutory approach and uses a verdict study where the author analyzes the rejection of life insurance based on the "Contestable Period" clause. The legal material in writing this research consists of 3 (three) parts, namely primary, secondary and tertiary legal materials are the basic materials that are used as a reference or foothold in this writing. Primary legal materials consist of laws and regulations and judges’ decisions, while secondary legal materials are obtained from books and other literature, tertiary legal materials in the form of interviews, legal dictionaries and internet sites related to this research.